Examining the impact of salesperson interpersonal mentalizing skills on performance: the role of attachment anxiety and subjective happiness. Issue 2 (2nd April 2016) - Agnihotri, Raj; Vieira, Valter Afonso; Senra, Karin Borges; Gabler, Colin B.
Abstract : Due to the dynamic and interpersonal nature of selling, understanding affective and cognitive relationships and their influence on performance has gained the attention of sales scholars. Moreover, recent literature has created opportunities to study the impact of cognitions, such as salesperson theory-of-mind, on sales performance. This research develops a model involving salesperson interpersonal mentalizing skills (i.e. rapport building, detecting nonverbal cues, taking a bird's-eye view, shaping the interactions), subjective happiness, attachment anxiety, and sales performance. Although salesforce optimization is critical in any economy, emerging economies are the growth frontier for many global companies. Using three samples from Brazil, we investigate the telecom, banking, and retail industries, providing generalizable results from one such emerging economy. We find that, in general, it is the influence of attachment anxiety and subjective happiness on interpersonal mentalizing skills which ultimately impacts sales performance. Based on these findings, we discuss several theoretical and managerial implications.